Modular assembly of the principal microtubule nucleator γ-TuRC - Würtz, Martin; Župa, Erik; Atorino, Enrico; Neuner, Annett; Böhler, Anna; Rahadian, Ariani S.; Vermeulen, Bram J. A.; Tonon, Giulia; Eustermann, Sebastian; Schiebel, Elmar; Pfeffer, Stefan (Nature Communications, 2022)
The human microtubule nucleator γ-TuRC is composed of more than thirty subunits, including actin. Here the authors reveal the structural mechanism of modular γ-TuRC assembly and show a functional role of actin in microtubule nucleation.